Reimagining the Gran Chaco : identities, politics, and the environment in South America - Hirsch, Silvia María; Canova, Paola; Biocca, Mercedes (University of Florida Press, 2021)
"This volume traces the socioeconomic and environmental changes taking place in the Gran Chaco, a vast and richly biodiverse ecoregion at the intersection of Argentina, Bolivia, Brazil, and Paraguay. Representing a wide range of contemporary anthropological scholarship that has not been available in English until now, Reimagining the Gran Chaco illuminates how the region's many Indigenous groups are negotiating these transformations in their own terms. The essays in this volume explore how the region has become a complex arena of political, cultural, and economic contestation between actors that include the state, environmental groups and NGOs, and private businesses and how local actors are reconfiguring their subjectivities and political agency in response. With its multinational perspective, and its examination of major themes including missionization, millenarian movements, the Chaco war, industrial enclaves, extractivism, political mobilization, and the struggle for rights, this volume brings greater visibility to an underrepresented, complex region." --